Exploring the Views and Dietary Practices of Elderly Nepalese Citizen: A Qualitative Study - Ghimire, Maya Nath (Nepal Journal of Multidisciplinary Research, 2021)
One of the main causes of morbidity and mortality of old-age people is malnutrition. We have very less studies on Nepalese elder citizen’s food practice. The aim of this study is to explore food practice of Nepalese elder citizen. A qualitative study was performed using in-depth interviews.The study was conducted in two districts of Nepal: Lamjung and Chitawan. All the respondents were 71-91 years elder citizen. The findings show that almost adolescents’ normal wakeup time is 4-5 AM. They consume tea, biscuits, milk, chapatti, beaten rice as breakfast; pulse, vegetable, milk, butter and weekly meat with normal food for lunch and dinner. Generally, they consume gravy vegetable curry with rice and chapatti. However, they prefer vegetarian soft and hot food.